The Impact Of Coffee Seed Assistance On Increasing Farmers' Income In West Java - Dudung Ahmad Suganda; Dina Dina; Iin Endah Setyawati (Jurnal Manajemen Pelayanan Publik, 2024)
Certified superior coffee seeds are difficult for farmers to obtain, even though certified superior seeds are a key factor in increasing productivity. This study aims to explore the impact of certified high-yielding seed assistance to coffee farmer groups to increase their income. This research uses a descriptive qualitative approach. The study population was all coffee farmers in West Java who received coffee seed assistance as many as six hundred and sixty farmer groups, and the sample was determined by sixty-six farmer groups from thirteen districts. Data were obtained through interviews, observations, and documentation studies. Data analysis using triangulation. The increase in coffee farmers' income is obtained from production sold in the form of green beans, resulting from the implementation of cultivation techniques in accordance with technical operational standards, technical guidance of officers, and the use of certified superior seeds. The use of certified superior seeds to coffee farmers can be replicated into a stimulant assistance model for empowering farmers to increase income from increasing coffee production and seed entrepreneurship. The impact of seed assistance is not only on increasing farmers' income, but also on improving hatchery implementation skills and increasing their capacity to become seed producers and suppliers of wider community needs.